Effect of humidity and contaminants on dry band formation in Outdoor Distribution Current Transformer 20 kV - Zaputra, Satia (LPPM Universitas Andalas, 2021)
This study reports the effect of humidity and pollutants on the formation of dry band phenomena on the insulation surface of an outdoor 20 kV distribution current transformer. From the results of measurements at high humidity 95% and high conductivity 36 mS/cm at a working voltage of 2-20kV test there is a change in the curve of increasing the value of the leakage current which is very volatile. Wet layer of impurity will cause a drastic decrease in surface resistance resulting in a large increase in leakage current. At a high conductivity of 36 mS/cm, the results of the measurement of surface resistance at low humidity of 55% worth 30.2 giga ohms decreased to 2.1 giga ohms at high humidity of 95%. While the value of the leakage current curve is very fluctuating from the value of 206 - 678 A at high conductivity with heavy pollutants. This information confirms the hypothesis that the boundary region of the two air-solid dielectrics of the epoxy resin causes surface discharge problems in dry band formation due to an increase in the non-uniform local electric field in the impurity layer adhering to the surface of the distribution current transformer. Keywords : leakage current, dry band, surface discharge, contaminants